Investigation of Lewis Acid-Base Reaction of Acidic Species Present in Aluminum Chloride-Urea Ionic Liquid [AlCl2.nUrea] + - Abood, Hadi M A; Fadhil, Marwa H (Al-Nahrain Journal of Science, 2018)
Aluminum chloride-urea ionic liquid was investigated for its active species concentration with the aide of electronic spectroscopy by Lewis acid-base titration with chloride ions. A coordination bonds between aluminum cationic species of the ionic liquid and the aromatic ring of toluene or benzene was assumed to be responsible for new formed bands in visible and ultraviolet regions. Upon Lewis acid-base titration these bands disappeared and the concentration of the acidic species were elucidated to be around 75 mole% of the initial aluminum chloride used to prepare a 1.5 mole aluminum chloride to 1 mole urea ionic liquid. The product of this reaction assumed to be between 1 acidic species to 1 chloride ion according to the mole fraction elucidated graph.